Depresión y su relación con la baja autoestima de un adolescente de 20 años - Arias Alencastro, Marcelo Moises (2022)
In everyday life we can find many difficulties and changes in the academic system, finishing going through a pandemic which changed the study modality, making it easier and more difficult for many students to access primary, secondary and higher levels, in this case it is presents as a subject of study a twenty-year-old adolescent who, as a consequence of everything in the study modality during, and the disadvantages that come with it, the change of environment the study triggers, depression and low self-esteem at the time of being self-sufficient , self-taught since they are lost in information depending on the case. These situations are what influence low self-esteem, techniques are used to collect information, such as interviews, observation, psychometric batteries and later a psychotherapeutic scheme is designed, which is the plan that is followed to work with the patient where They use behavioral cognitive techniques that allow identifying the thought that generates depression and low self-esteem, with the guidance of the tutor, they can develop an alternative objectively.